Bite by a juvenile Bothrops venezuelensis (Venezuelan lancehead) resulting in severe envenomation: A case report. (June 2020) - Fuchs, Joan; Faber, Katrin; Tuchscherer, Daniel T.; Tsakiris, Dimitrios A.; Weiler, Stefan; Hofer, Katharina E.
Abstract: Bothrops venezuelensis is a venomous snake of the Viperidae family. It is associated with a high snakebite-related morbidity and mortality in Venezuela, although clinical case descriptions are scarce. Bites by other Bothrops sp . can result in coagulopathy and acute kidney injury. We describe a bite by a captive juvenile B. venezuelensis that caused local swelling, severe pain, endothelial damage, excessive fibrinolysis (INR >12, aPTT 136s, fibrinogen 0.3g/l) and incoagulable blood within 1.5 hours after the bite. The patient was treated with prothrombin complex factors concentrate, fibrinogen and antivenom (Antivipmyn®, Instituto Bioclon, Mexico) 4.5 h after the bite, which improved coagulation parameters progressively. Subsequently signs of compensated disseminated intravascular coagulation manifested and the patient received fresh frozen plasma and erythrocyte concentrate. The patient developed acute kidney injury with macroscopic hematuria. Fluid overload resulted in pulmonary edema requiring intermittent ventilation and diuretic treatment with furosemide. He was discharged with moderately elevated creatinine 16 days after hospitalization. Creatinine level normalized within another week. This case displays the life-threatening toxicity even after juvenile B. venezuelensis bites and the comparability to bites by other Bothrops sp . Highlights: Describes a life-threatening envenomation by a juvenile Bothrops venezuelensis . The patient developed severe hematotoxicity, acute kidney injury and pulmonary edema. He was treated with antivenom and required intermittent non-invasive ventilation. The toxicity profile of B. venezuelensis seems to be comparable to other Bothrops sp.